2020
DOI: 10.1002/glia.23957
|View full text |Cite
|
Sign up to set email alerts
|

Kif3a deletion prevents primary cilia assembly on oligodendrocyte progenitor cells, reduces oligodendrogenesis and impairs fine motor function

Abstract: Primary cilia are small microtubule‐based organelles capable of transducing signals from growth factor receptors embedded in the cilia membrane. Developmentally, oligodendrocyte progenitor cells (OPCs) express genes associated with primary cilia assembly, disassembly, and signaling, however, the importance of primary cilia for adult myelination has not been explored. We show that OPCs are ciliated in vitro and in vivo, and that they disassemble their primary cilia as they progress through the cell cycle. OPC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 116 publications
(179 reference statements)
4
36
0
Order By: Relevance
“…It was further found that primary cilia of OPCs were disassembled during differentiation into OLGs ( Falcon-Urrutia et al, 2015 ). Notably, in a mouse model, depletion of KIF3A in OPCs inhibited OLG proliferation and differentiation by affecting cilia-dependent Shh signaling and subsequently induced motor defects due to a decrease in myelinated axons ( Cullen et al, 2021 ). Interestingly, the abnormal length of primary cilia in OPCs led to impairment of OLG differentiation ( Dugas et al, 2010 ; Hudish et al, 2016 ).…”
Section: Primary Cilium In Oligodendrocytes: a Key Mediator For Myelination In The Central Nervous Systemmentioning
confidence: 99%
“…It was further found that primary cilia of OPCs were disassembled during differentiation into OLGs ( Falcon-Urrutia et al, 2015 ). Notably, in a mouse model, depletion of KIF3A in OPCs inhibited OLG proliferation and differentiation by affecting cilia-dependent Shh signaling and subsequently induced motor defects due to a decrease in myelinated axons ( Cullen et al, 2021 ). Interestingly, the abnormal length of primary cilia in OPCs led to impairment of OLG differentiation ( Dugas et al, 2010 ; Hudish et al, 2016 ).…”
Section: Primary Cilium In Oligodendrocytes: a Key Mediator For Myelination In The Central Nervous Systemmentioning
confidence: 99%
“…proliferation, as suggested by Cullen et al (2020). However, this result also suggests that PC could be implicated in transition from proliferative to differentiating stages.…”
Section: Discussionmentioning
confidence: 49%
“…To identify new components involved in Hh signaling transduction, we isolated the mouse embryonic fibroblasts (MEFs) and seeded them in different densities to make MEFs deciliated or ciliated and biochemically extracted total membrane proteins from the deciliated MEFs in low densities as well as the ciliated MEFs in high densities (Figure 1 A-B). Data of liquid chromatography-tandem mass spectrometry (LC-MS/MS) with normalization to protein content revealed that, compared with the deciliated MEFs, the ciliated MEFs are enriched in acetylated tubulin (Ac-Tub) and Arl13b, two markers for primary cilia 23 , 24 , and IFT88 and KIF3A as well, two molecules pivotal to the maintenance and function of primary cilia 25 , 26 (Figure 1 C). Intriguingly, among the three members in Rho family of small GTPases 27 , only enrichment of Rac1 but not Cdc42 or RhoA was observed in the ciliated MEFs, compared with that in deciliated MEFs (Figure 1 C), and the enrichment of Rac1 in MEF primary cilia was additionally verified by immunnofluorescent staining (Figure 1 D), indicating that Rac1 may affect Hh signaling.…”
Section: Resultsmentioning
confidence: 99%